EFFECTIVENESS OF FERMENTATION OF FEED WITH DIFFERENT PROTEINS ON BIOFLOCK SYSTEM ON GROWTH TILAPIA (Oreochromis niloticus) - Satria Ari Sahendra; Nunik Cokrowati; Andre Rachmat Scabra (University of Lampung, 2023)
Tilapia (Oreochromis niloticus) is a well known aquaculture fish commodity in Indonesia. The fermentation process of feed is a technology to increase the protein of raw materials. The purpose of this research is to find out and evaluate the effect of feed fermentation on survival, long and heavy growth, feed conversion, protein retention and water quality on tilapia who maintenance with bioflok system. The study was conducted for 60 days using tilapia fish with an average length of 5 cm and an average weight of 2 grams / tail, then maintained with a bioflok system. The treatment will be fermented for 1 day using EM4 in feed with 25%, 20%, 15%, and 25% unfermented protein feed control. The results of this study showed a real influence on the absolute long growth parameters with the highest values in P2 with a value of 2.4 cm and the lowest in P3 and P4 with the same value of 1.8 cm. at the specific long growth rate the highest value at P2 is 0.86%/day and the lowest in P3 and p4 with the same value of 0.7%/day. Then protein retention, the best treatment value is in P2 with a value of 5.5% and the lowest in P4 with a value of 3.1%.